High Chemical Potential Driven Amorphization of Pd‐based Nanoalloys. Issue 4 (12th March 2023) - Jiang, Qiaorong; Dong, Yongdi; Lü, Linzhe; Zheng, Zhiping; Nan, Zi‐Ang; Ye, Jinyu; Lin, Haixin; Jiang, Zhiyuan; Xie, Zhaoxiong
Abstract: Amorphous metals and alloys are promising candidates for superior catalysts in many catalytic and electrocatalytic reactions. It is of great urgency to develop a general method to construct amorphous alloys and further clarify the growth mechanism in a wet‐chemical system. Herein, inspired by the conservation of energy during the crystallization process, amorphous PdCu nanoalloys have been successfully synthesized by promoting the chemical potential of the building blocks in solution. Benefiting from the abundant active sites and enhanced corrosion resistance, the synthesized amorphous PdCu nanostructures exhibit superior catalytic activity and durability over the face‐centered cubic one in formic acid decomposition reaction. More importantly, the successful fabrications of amorphous PdFe, PdCo, and PdNi further demonstrate the universality of the above strategy. This proposed strategy is promising to diversify the amorphous family. Abstract : Deduced from the energy conservation theory, this work proposes that nanoalloys prefer to be amorphous when grown in a solution with high chemical potential, in contrast, the products will be crystalline. It is demonstrated by three methods, including varying the amount and the adding speed of reductant, and the stirring rate, to control the phase of the Pd‐based nanoalloys.